Low temperature dissolution of yeast chitin-glucan complex and characterization of the regenerated polymer - Araújo, Diana (2020)
Chitin-glucan complex (CGC) is a copolymer composed of chitin and glucan moieties extracted from the cell-walls of several yeasts and fungi. Despite its proven valuable properties, that include antibacterial, antioxidant and anticancer activity, the utilization of CGC in many applications is hindered by its insolubility in water and most solvents. In this study, NaOH/urea solvent systems were used for the first time for solubilization of CGC extracted from the yeast Komagataella pastoris. Di erent NaOH/urea ratios (6:8, 8:4 and 11:4 (w/w), respectively) were used to obtain aqueous solutions using a freeze/thaw procedure. There was an overall solubilization of 63–68%, with the highest solubilization rate obtained for the highest tested urea concentration (8 wt%). The regenerated polymer, obtained by dialysis of the alkali solutions followed by lyophilization, formed porous macrostructures characterized by a chemical composition similar to that of the starting co-polymer, although the acetylation degree decreased from 61.3% to 33.9–50.6%, indicating that chitin was converted into chitosan, yielding chitosan-glucan complex (ChGC). Consistent with this, there was a reduction of the crystallinity index and thermal degradation temperature. Given these results, this study reports a simple and green procedure to solubilize CGC and obtain aqueous ChGC solutions that can be processed as novel biomaterials